One‐Year Outcomes Associated With Using Observation Services in Triaging Patients With Nonspecific Chest Pain. Issue 10 (11th August 2014) - Abbass, Ibrahim M.; Virani, Salim S.; Michael Swint, J.; Chan, Wenyaw; Franzini, Luisa
Abstract Background Observation services are provided in greatly variant settings. The aim of this study was to reexamine the effectiveness of observation services compared to inpatient units for patients with nonspecific chest pain. Hypothesis Patients admitted to observation units have similar outcomes to patients admitted to inpatient wards. Methods We conducted a claim‐based retrospective study for 7549 patients who were admitted to observation and inpatient units. Both models of care were evaluated using the 1‐year costs related to chest pain/cardiovascular diseases, and primary and secondary outcomes. Primary outcome was a composite of myocardial infarction, congestive heart failure, stroke, or cardiac arrest, whereas secondary outcomes included revascularization procedures, emergency room revisits, and hospitalization due to cardiovascular diseases. Results Two‐thirds (65.7%, n = 4962) of patients in the sample had observation services, and 34.3% (n = 2587) were admitted to inpatient care. Of the inpatient group, 4.9% experienced a total of 167 primary outcomes, whereas 14.1% experienced a total of 571 secondary outcomes. In comparison, 3.8% of the observation group experienced 238 primary outcomes, and 10.3% experienced 737 secondary outcomes. After adjusting for baseline characteristics using Cox proportional hazard and quantile regression models, no differences between the 2 groups were detected in the 1‐year costs of cardiovascular services and primary or secondary outcomes. Patients who had observation services were 79% (95% confidence interval: 1.24‐2.58) more likely to have revascularization procedures compared to those admitted to inpatient care. Conclusions Patients who had observation services had similar outcomes and 1‐year costs compared to patients admitted to inpatient wards.